2019
DOI: 10.7189/jogh.09.010415
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and perceptions of women regarding human rights related to maternal health in rural Bangladesh

Abstract: Background The global development community has increasingly come to frame preventable maternal mortality and morbidity principally as a violation of women’s basic human rights, necessitating a human rights-based approach to be appropriately addressed. In this article, we explore how human rights are understood and perceived in relation to maternal health at the local level in rural Bangladesh. This is essential given the momentum at the global level to promote rights and apply rights-based approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…These constraints include existing policies disallowing or limiting labour companion support, physical space constraints, perceived risk of infection, and perceived need for training of labour companions before birth [2,94]. Moreover, women may not be aware of their rights to receive quality maternity care and the importance of labour companionship, which can be addressed through antenatal education programmes or in community discussions [95]. Existing implementation research projects and programmes have addressed context-specific constraints to introduce labour companionship in different settings, for example, by using participatory approaches with health workers and with community stakeholders, making physical changes to the labour ward environment, and orienting health workers, women, and potential companions about how to best support women [92,96,97].…”
Section: Implications For Policy Practice Monitoring and Researchmentioning
confidence: 99%
“…These constraints include existing policies disallowing or limiting labour companion support, physical space constraints, perceived risk of infection, and perceived need for training of labour companions before birth [2,94]. Moreover, women may not be aware of their rights to receive quality maternity care and the importance of labour companionship, which can be addressed through antenatal education programmes or in community discussions [95]. Existing implementation research projects and programmes have addressed context-specific constraints to introduce labour companionship in different settings, for example, by using participatory approaches with health workers and with community stakeholders, making physical changes to the labour ward environment, and orienting health workers, women, and potential companions about how to best support women [92,96,97].…”
Section: Implications For Policy Practice Monitoring and Researchmentioning
confidence: 99%
“…As opined by Castillo (2022), most female informal workers in the Philippines underwent the challenge on lack of information as regards their rights. However, the study conducted by Perkins et al (2019) showed that over two-thirds of Bangladeshi women research participants were aware that they have rights pertaining to maternal health, but very few (less than 10%) can enumerate at least three specific rights concerning maternal health. Similarly, in a study conducted by Shaikh (2020) in Pakistan, female research participants also had minimal knowledge about their country's laws for protecting women, which can be due to plain negligence, at least from the perspectives of academics.…”
Section: "I Don't Have Any Idea I Haven't Even Heard That One I Forgo...mentioning
confidence: 99%
“…Segundo os relatos de experiências colhidos durante pesquisa realizada por Oliveira et al (2019), as mulheres que vivenciaram experiências dolorosas, carregaram marcas além das cicatrizes, mas não sabiam ao menos caracterizar a violência obstétrica ou mesmo informar em que momento sofreram. Perkins et al (2019) afirmam que a conscientização e entendimento que as mulheres têm sobre direitos humanos e relacionados à saúde materna, assim como o aumento da assistência durante o pré-natal, estão intimamente ligados à maiores níveis de escolaridade e riqueza, sugerindo que as intervenções de saúde promovam a conscientização dos direitos humanos relacionados à saúde materna, de forma abrangente e apropriada nas comunidades a fim de melhorar a saúde materna.…”
Section: Conhecimento Das Mulheres Sobre Seus Direitos No Período Gestacional E Puerperalunclassified